Mediating role of loneliness and emotional disturbance in the association between childhood trauma and occupational burnout among nurses: a cross-sectional study - Hu, Jing; Zhai, Mengxi; Fu, Donghui; Duan, Zhizhou; Chen, Xiangfan (Frontiers in Psychiatry, 2024)
Background The occupational burnout status of nurses in China warrants attention. Childhood trauma, loneliness, and emotional disturbance are significant predictors of this burnout, yet few studies have delved into the underlying mechanisms. This study seeks to explore the mediating pathway from childhood trauma to loneliness, emotional disturbance, and ultimately occupational burnout among nurses through a cross-sectional analysis. Method Data for the study were collected from Yunnan province, China, from 11 July to 26 July 2022. Key variables were measured using standardized scales: the Childhood Trauma Questionnaire Short Form for childhood trauma, the three-item loneliness scale for loneliness, the Patient Health Questionnaire and the Generalized Anxiety Disorder questionnaire for emotional disturbance, and the Maslach Burnout Inventory-Human Service Survey for occupational burnout. Mediation modeling analysis was employed for data analysis to test the effect of loneliness and emotional disturbance on the association between childhood trauma and occupational burnout. Data analysis was conducted using AMOS and SPSS software. Results Loneliness and emotional disturbance fully mediated the association between childhood trauma and emotional exhaustion [indirect effect (95% CI) = 0.228 (0.196, 0.270)]. Loneliness and emotional disturbance partially mediated the association between childhood trauma [indirect effect (95% CI) = −0.020 (−0.039, 0.002)] and personal accomplishment or depersonalization [indirect effect (95% CI) = 0.221 (0.186, 0.255)]. Conclusion Childhood trauma could affect occupational burnout through loneliness and emotional disturbance among nurses. Preventive strategies could include protective interventions like treatment of loneliness and emotional disturbance, especially in nurses who experienced childhood trauma.